220k views
1 vote
What is the solution to -6 + 5(1-x) = - 13 – 7 x?

2 Answers

1 vote
sorry this so sloppy, hope this helps!!
What is the solution to -6 + 5(1-x) = - 13 – 7 x?-example-1
User Chris Hatton
by
5.0k points
4 votes

Answer:

x=-6

Explanation:


-6+5(1-x)=-13-7x

1) Using the distributive property distribute the 5 to the equation in the parenthesis


-6+5-5x=-13-7x

2) Combine the -6 and 5


-1-5x=-13-7x

3) Add 1 to both sides.


-1(+1)-5x=-13(+1)-7x


-5x=-12-7x

4) Add 7x to both sides


-5x(+7x)=-12-7x(+7x)\\ 2x=-12

5) Divide both sides by 2 to isolate the x.


(2x)/(2) =(-12)/(2)\\ x=-6

User Sergzach
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.